Is the information sufficient 6?

Algebra Level 3

For f ( x ) f(x) is defined at x ( 1 , ) x \in (1, \infty) , f ( x ) > 1 f(x) > 1 and the function f ( x ) f(x) is a one-to-one relation. Also, f ( x ) f ( f ( x ) + 2016 x ) = 2016 f(x) \cdot f\left(f(x) + \dfrac{2016}{x} \right) = 2016 for all such x x .

Evaluate:

65 ( ( ( 2017 f ( 2017 ) 1008 ) 2 m o d 2017 ) + 1 ) 65 \cdot \left(\left(\left(2017f(2017) - 1008\right)^2 \bmod 2017 \right) + 1\right)


For more problems like this, try answering this set .


The answer is 98475.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Christian Daang
Jun 30, 2017

Let f ( 2017 ) = a f(2017) = a . Suppose x = 2017 a f ( a + 2016 2017 ) = 2016 f ( a + 2016 2017 ) = 2016 a x = 2017 \implies af\left(a + \dfrac{2016}{2017}\right) = 2016 \implies f\left(a + \dfrac{2016}{2017}\right) = \dfrac{2016}{a}

Suppose x = a + 2016 2017 2016 a f ( 2016 a + 2016 a + 2016 2017 ) = 2016 f ( 2016 a + 2016 a + 2016 2017 ) = a x = a + \dfrac{2016}{2017} \implies \dfrac{2016}{a}f\left(\dfrac{2016}{a} + \dfrac{2016}{a + \dfrac{2016}{2017}}\right) = 2016 \implies f\left(\dfrac{2016}{a} + \dfrac{2016}{a + \dfrac{2016}{2017}}\right) = a

Since f ( x ) f(x) is one-to-one, 2016 a + 2016 2017 2017 a + 2016 = 2017 ( 2016 2017 a ) + 201 6 2 + ( 2016 2017 a ) = 201 7 2 a 2 + ( 2017 2016 a ) 201 7 2 a 2 ( 2016 2017 a ) 201 6 2 = 0 a = ( 2016 2017 ) ± 201 6 2 201 7 2 + ( 4 201 7 2 201 6 2 ) 2 201 7 2 = 1008 ± 1008 5 2017 \implies \dfrac{2016}{a} + \dfrac{2016\cdot2017}{2017a + 2016} = 2017 \implies (2016\cdot2017a) + 2016^2 + (2016\cdot2017a) = 2017^2a^2 + (2017\cdot2016a) \\ \implies 2017^2a^2 - (2016\cdot2017a) - 2016^2 = 0 \implies a = \dfrac{(2016\cdot2017) \pm \sqrt{2016^22017^2 + (4\cdot2017^2\cdot2016^2)}}{2\cdot2017^2} = \dfrac{1008 \pm 1008\sqrt{5}}{2017}

Since f ( x ) > 1 for all x > 1 f(x) > 1 \ \text{for all x > 1} , a = f ( 2017 ) = 1008 + 1008 5 2017 \implies a = f(2017) = \dfrac{1008 + 1008\sqrt{5}}{2017}

65 ( ( ( 2017 f ( 2017 ) 1008 ) 2 m o d 2017 ) + 1 ) = 65 ( ( ( 2017 1008 + 1008 5 2017 1008 ) 2 m o d 2017 ) + 1 ) = 65 ( ( ( 1008 5 ) 2 m o d 2017 ) + 1 ) = 98475 . \begin{aligned} \therefore 65 \cdot \left(\left(\left(2017f(2017) - 1008\right)^2 \bmod 2017 \right) + 1\right) &= 65 \cdot \left(\left(\left(2017\cdot \dfrac{1008 + 1008\sqrt{5}}{2017} - 1008\right)^2 \bmod 2017 \right) + 1\right) \\ & = 65 \cdot \left(\left((1008\sqrt{5})^2 \bmod 2017 \right) + 1\right) = \boxed{98475} . \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...